Educação das relações étnico-raciais, arte e memória: refletindo sobre a formação e atuação de professores - Rosa, Tifany Cristina Rodrigues (Universidade Federal de São Carlos, 2023)
Racism is a reality founded on the social structures of Brazil. Education is not isolated to this process, so the training of teachers faced with social contradictions became necessary. This work aims to establish connections with the use of Art in the instrumentalization of teacher training processes, aiming at the implementation of Brazilian Laws 10.639/03 and 11.645/08 within schools. The study has a qualitative and critical bias, and brings data collected with the application of questionnaires with 22 teachers and school principals who work in schools located in the State of São Paulo, in order to positively consider the use of Art and Memory as possible resources in teacher training environments.
Education of ethnic-racial relations, art and memory: reflecting on the formation and performance of teachers
Keywords: Educação das Relações Étnico-raciais; Formação Docente; Arte e Memória; Education and the Ethnic-racial relations; Teacher Training; Art and Memory; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO